Ill. Act of Apr. 16, 1881, as codified in Ill. Stat. Ann., Crim. Code 73 (1885), ch. 38, Possession or sale forbidden, § 1 - (:unkn) unknown (General Publisher, 1881)
Prohibited the possession, selling, loaning, or hiring for barter of a slungshot or metallic knuckles or other deadly weapon. Punishable as a misdemeanor.
--
Keywords: TRANSFER & POSSESSION